A model study of pile groups in clay - Budak, Faruk. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
A model scale study of the bearing capacity of single piles and pile groups with a small L/D ratio in clay under vertical and axial loads has been performed. It was investigated how the pile spacing, driving energy, number of piles and time factor effects the bearing capacity of pile groups. Experimental results have been compared with the theoretical values. In this study for the interpretation of test results, a statistical analysis method called Latin Square was used.
Keywords: Piling (Civil engineering); Clay soils.